(untitled) (Nóema, 2011)
Dalla Lebenswelt di Husserl alla possibilità pratica di una nuova via filosofica. La rivalutazione della doxa e del senso comune. Vita materiale e pensiero delle pratiche. The little beginning: material life and reality From the question of Lebenswelt in Husserl to the possibility of a new way of philosophing. The revaluation of doxa and common-sense. Material life and the thought of practices.